Impact of Shanghai FTZ (Free Trade Zone) Policy on housing prices: a study based on open data - Longxu, Yan; Qianhui, Jin (AESOP, 2016)
This paper extracts information of 205 valid community samples located around the first Shanghai Free Trade Zone from open data of related websites, including historical average price of each community from March 2013 to May 2015, as well as the characteristics of each cell. After measuring the impact of all factors with Hedonic model by month, we found that house prices is more sensitive to FTZ policy than others. And the impact by month which is measured by the coefficient of distance to Free Trade Zone in the Hedonic model can be divided into seven stages, including two rapid increase stages ,three falls and eventually stable fluctuation stage, which are in perfect accordance with the information disclosure process of FTZ policy of Shanghai. The results show that the impact of the FTZ policy or the information disclosure on house prices in the peak is about three times of the initial period, which gradually return stably fluctuations, and ultimately is about two times of the initial period. The eventual impact in stably fluctuation stage is that housing prices increase by 2.81% for every kilometer closer to the Free Trade Zone.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south